Profiles of Temperature and Density Based on 1- and 10-Percent Extremes in the Stratosphere and Troposphere - Kantor, A. J.; Tattelman, P. (1984)
Vertical profiles of temperature and density have been developed based on 1 and 10 percent warm and cold temperatures and 1 and 10 percent high and low densities occurring at the worst locations in the world (except Antarctica) during the worst month. The profiles, from the surface to 80 km, are based on extremes that occur at 5, 10, 20, 30, and 40 km. For example, one of the temperature profiles developed was based on a 10 percent warm temperature at an altitude of 20 km; thus, it represents meteorological conditions typically associated with this extreme. Ten such warm profiles (5 levels by 2 percentiles) and 10 cold profiles have been constructed from 14 years of rawinsonde and rocketsonde observations. Internally consistent hydrostatic profiles of density associated with these temperature profiles are provided. Twenty analogous density (and associated temperature) profiles also have been developed from extreme densities occurring at these altitudes. Thus, a set of realistic profiles (rather than envelopes) of temperature and density associated with extremes at specified levels in the troposphere and stratosphere are available for altitudes up to 80 km. Keywords: Atmospheric profiles; Extreme atmospheres; Temperature profiles; Density profiles; Thermodynamic properties.